2013
DOI: 10.1007/s00132-013-2182-1
|View full text |Cite
|
Sign up to set email alerts
|

Hüftdysplasie und Morbus Scheuermann bei einem Mädchen mit Typ-II-Kollagenopathie

Abstract: Hip dysplasia and Scheuermann's osteochondritis have never been reported in connection with a mutation in COL2A1 (collagenopathy type II). Awareness is needed for careful phenotypic and genotypic characterization in patients with irritable hip pain and spinal stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Three fetuses were found to have heterozygous mutations of COL2A1 (c.1636G>A, c.1070 G>C, c.4A>T), which have been associated with various types of osteogenic dysplasia (Deng, Huang, & Yuan, 2016). (Al Kaissi et al, 2013) described a patient with a c.1636G>A mutation of COL2A1 who presented with hip dysplasia and spinal osteochondritis. The COL2A1 mutation c.1070G>C, which was found in fetus 23, has been associated with protein effects by bioinformatics predictive analysis, leading us to conclude that this mutation is likely pathogenic, although further study is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Three fetuses were found to have heterozygous mutations of COL2A1 (c.1636G>A, c.1070 G>C, c.4A>T), which have been associated with various types of osteogenic dysplasia (Deng, Huang, & Yuan, 2016). (Al Kaissi et al, 2013) described a patient with a c.1636G>A mutation of COL2A1 who presented with hip dysplasia and spinal osteochondritis. The COL2A1 mutation c.1070G>C, which was found in fetus 23, has been associated with protein effects by bioinformatics predictive analysis, leading us to conclude that this mutation is likely pathogenic, although further study is needed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, marked metaphyseal abnormalities were noted in one of our patients (III-3), which was distinct from the phenotypes of Xu et al’s patients. Kaissi et al reported another patient of a c.G1636A mutation in a patient in Germany [21]. As the authors stated in the English abstract, the patient was characterized by short stature associated with acetabulo femoral dysplasia, spinal osteochondritis (Scheuermann’s disease), and mild thoracic kyphosis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a patient harboring an Arg 75 -Cys mutation in the collagen type II alpha 1 ( COL2A1 ) gene was found to experience childhood-onset progressive osteoarthritis and vertebral changes, similar to Scheuermann’s disease [ 18 ]. Another mutation in the COL2A1 gene (c.1636G > A, p.G546S) was detected in a girl presenting with hip dysplasia and Scheuermann’s osteochondritis [ 19 ]. The tryptophan allele of the collagen type IX alpha 3 ( COL9A3 ) gene has also been associated with Scheuermann’s disease and intervertebral disk degeneration [ 20 ].…”
Section: Discussionmentioning
confidence: 99%